ANSWER :
a. The derivative is :
![f^(\prime)(x)=12x^(2)-(6)/(x^(3))](https://img.qammunity.org/2023/formulas/mathematics/college/cto1op6a52oi240rgr8syc93nsl853hvs6.png)
b. The point on the graph is (1, 4)
EXPLANATION :
From the problem, we have the function :
![f(x)=4x^3+(3)/(x^2)-3](https://img.qammunity.org/2023/formulas/mathematics/college/sjuo6d3flcmxtj22hl40nnz77iw466culw.png)
a. The derivative will be :
![\begin{gathered} f^(\prime)(x)=3(4x^2)+(-2)((3)/(x^3)) \\ f^(\prime)(x)=12x^2-(6)/(x^3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/npar0a0pv7iyvoqr6y4qb0x6904o2iphah.png)
b. The gradient of the tangent is also the derivative which is f'(x)
So we need to find the point in which f'(x) = 6
That will be :
![\begin{gathered} 6=12x^2-(6)/(x^3) \\ \text{ Multiply both sides by x\textasciicircum3} \\ 6x^3=12x^5-6 \\ \text{ Divide both sides by 6} \\ x^3=2x^5-1 \\ x^3-2x^5=-1 \\ 2x^5-x^3=1 \\ x^3(2x^2-1)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rer2fx32185ch4chi4p96n8zg8ob5zk1wc.png)
Equate both factors to 1 :
![\begin{gathered} x^3=1 \\ x=1 \\ \\ 2x^2-1=1 \\ 2x^2=2 \\ x^2=1 \\ x=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/56i8mjgzv4nnl8wjk8ye2bxz1t3dxguoay.png)
So we have x = 1
Substitute x = 1 to the original function :
![\begin{gathered} f(1)=4(1)^3+(3)/((1)^2)-3 \\ f(1)=4+3-3 \\ f(1)=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rm5ajlzh0wdn0ytb8l5zpuo213h9wkgr82.png)
Therefore the point is (1, 4)